The Domination of the Local Party of Aceh Parliament in Responding the Aspiration of Community - Sayed Amirulkamar; Ismail Ismail (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
The Unitary State of the Republic of Indonesia as a country of island diversity, culture, ethnicity, language and others which makes Indonesia political power does not adhere to the system of any country, but adopts the existence of the order of life of the Indonesian people by combining the "Trias Politica" government system, which presents by Montesquieu who was born on 18 January 1689 and died on February 10, 1755 at the age of 66, (French political thinkers) who lived in the Age of Enlightenment (English: Enlightenment) which describes power with the term "Separation of power" into three powers there are "Legislative" (Making Laws), "Executives" (Acting Laws ) and "Judicative" (Overseeing the laws) and not division of power. With this authority politically everyone understands the Legislative Election in Aceh, it different from legislative elections in various provinces in Indonesia, the difference in Aceh is that there are a number of local political parties who have competed in democratic parties since 2009. As for the legislative elections to the period 2019-2024 who have passed the verification of 4 (four) local political in the Aceh Party (PA), the Nanggroe Aceh Party (PNA), the Aceh Regional Party (PDA), and the SIRA Party who compete competitively for parliamentary seats (DPRA / DPRK).